The disconnects between myth and history and the fictional games in Manuel Scorza’s narrative - Lassus, Jean-Marie (2019)
The classification of “The Silent War” series (1970-1979) as “pro-indigenous literature” led to the epic nature of Manuel Scorza’s novels being overlooked, together with the complexity and richness of a literature that employs both the narrative device of the chronicle and the path opened by the new novel to explore the disconnects between myth and history. The “Immobile Dance” (1983), the first of a new series of novels entitled “The Fire and the Ash”, would continue to employ the epic form and the new forms of writing, inviting critical reflection on how Latin American literature is received in Europe.